THE INFLUENCE OF PRODUCT QUALITY, PROMOTIONS AND PRICES ON CONSUMER DECISIONS IN CHOOSING PADANG PUSAKO KARYA UJUNG MEDAN - Syaputra, Dadang; Yunus Fitriady, Mochamad; Syafriyandi, Syafriyandi; Telaumbanua, Faudunasokhi (Politeknik Negeri Media Kreatif, 2023)
This research aims to explain the influence of product quality, promotion and price on consumer decisions in choosing Padang Pusako Karya Ujung Medan Restaurant. The sample uses the Malhotra Formula. The data collection method used was by giving questionnaires to consumers of the Padang Pusako Karya Ujung Medan Restaurant. Data were analyzed using the Quantitative Method, namely using questionnaire reliability tests, classical assumption tests, multiple regression analysis, correlation analysis, F test and T test with the help of SPSS 22.00 for Windows software. The results of the research show that hypothesis testing shows that partially there is a significant influence between product quality (X1) and promotion (X2) on consumer decisions in choosing the Padang Pusako Karya Ujung Medan Restaurant, while the Price variable (X3) has no significant influence on the Decision variable. Consumers in choosing the Padang Pusako Karya Ujung Medan Restaurant. Testing the influence of the independent variables together (simultaneously) on the dependent variable is carried out using the F test, stating that the hypothesis states that there is a significant influence between product quality (X1), Promotion (X2), and Price (X3) on consumer decisions chose the Padang Pusako Karya Ujung Medan Restaurant. Keywords: Marketing Management, Product Quality, Promotion, Price, Consumer Decisions